The Dynamic Governance in the Implications of Mining Permit: A Case Study in Bawan Village, Agam Regency - Anggraini, Viska; Helmi , Rahmadhona Fitri (The Future of Education Journal, 2025)
This study focuses on analyzing the impact of the granting of a C-type mining permit in Nagari Bawan, Agam Regency, using a Dynamic Governance perspective that emphasizes three key elements: Thinking Ahead, Thinking Again, and Thinking Across. This study was conducted using a qualitative approach, with data collection conducted through in-depth interviews, direct field observations, and document reviews. The research findings reveal that in the Thinking Ahead aspect, there have been efforts at long-term planning through adjusting permits to spatial planning provisions and extensive involvement of the mining area. However, less than optimal information dissemination and outreach to the community remain problematic. In the Thinking Again aspect, technical agencies have conducted evaluations and imposed administrative sanctions for violations, but the implementation of social commitments such as road repairs has not been fully realized. Meanwhile, in the Thinking Across aspect, there is visible inter-institutional cooperation and the involvement of local actors such as the village government and some communities. However, community participation is generally still minimal and field supervision has not been carried out systematically. Overall, this study concludes that although the principles of Dynamic Governance have begun to be applied in the management of mining permits, their implementation still faces challenges in the aspects of community involvement, social evaluation, and strengthening oversight mechanisms.